A cost of living longer: Projections of the effects of prospective mortality improvement on economic support ratios for 14 advanced economies. (3rd May 2016) - Parr, Nick; Li, Jackie; Tickle, Leonie
Abstract : The economic implications of increasing life expectancy are important concerns for governments in developed countries. The aims of this study were as follows: (i) to forecast mortality for 14 developed countries from 2010 to 2050, using the Poisson Common Factor Model; (ii) to project the effects of the forecast mortality patterns on support ratios; and (iii) to calculate labour force participation increases which could offset these effects. The forecast gains in life expectancy correlate negatively with current fertility. Pre-2050 support ratios are projected to fall most in Japan and east-central and southern Europe, and least in Sweden and Australia. A post-2050 recovery is projected for most east-central and southern European countries. The increases in labour force participation needed to counterbalance the effects of mortality improvement are greatest for Japan, Poland, and the Czech Republic, and least for the USA, Canada, Netherlands, and Sweden. The policy implications are discussed.